CHALLENGES TO SPEAKING SKILLS ENCOUNTERED BY ENGLISH-MAJORED STUDENTS: STORY OF ENGLISH EDUCATION STUDY PROGRAM STATED ISLAMIC UNIVERSITY SULTHAN THAHA SAIFUDDIN JAMBI - Bayu Budi Dharma; Ordiatul Fitri (Universitas Khairun, 2022)
English speaking skills is an indispensable course in English language curriculum at tertiary level. However, it is notÂ easy for English learners in this context to achieve their fluency and proficiency in English speaking skill due to certain internal and external factors. Therefore, this study is to investigate challenges of speaking skills faced by English-majored At English Education Study Program Stated Islamic University Sulthan Thaha Saifuddin Jambi. The data obtained from the questionnaire with 81 students the results of this study showed that there are many challenges encountered by students in speaking English. Linguistic aspects such as fluency, pronunciation, and lack of vocabulary, grammar mastery are also parts of the challenges they faced in enhancing their English speaking.